2014
DOI: 10.4103/2152-7806.134912
|View full text |Cite
|
Sign up to set email alerts
|

Benign scalp lump as an unusual presentation of extranodal Rosai-Dorfman Disease

Abstract: Background:Rosai–Dorfman disease (RDD) is a rare benign histioproliferative disease. It is typically characterized by benign histiocyte proliferation with lymphadenopathy, fever, and leukocytosis and was first described in 1969 by Rosai and Dorfman. Extranodal involvement has been reported in approximately up to 43% of the cases with isolated central nervous system (CNS) manifestations being even rarer.Case Description:We report our management of a 41-year-old female with extranodalpurely CNS RDD presenting as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“… 5 Yoon et al 5 reported a patient with an initial bone lesion in the fibula who developed subcutaneous lesions on upper extremities several months later. Similar to our patient, 2 patients who presented with subcutaneous lesions on the scalp and underlying calvarial RDD have been reported recently 10 , 13 ; 1 of the patients also developed a lesion in the spine later. 13 Although it is unlikely the cutaneous lesion was derived from RDD of the bone in our patient, it is impossible to discriminate whether cranial erosion is a result of the local destruction of CRDD or concomitant primary RDD of the bone involving the overlying skin without obtaining a sample from cranium.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… 5 Yoon et al 5 reported a patient with an initial bone lesion in the fibula who developed subcutaneous lesions on upper extremities several months later. Similar to our patient, 2 patients who presented with subcutaneous lesions on the scalp and underlying calvarial RDD have been reported recently 10 , 13 ; 1 of the patients also developed a lesion in the spine later. 13 Although it is unlikely the cutaneous lesion was derived from RDD of the bone in our patient, it is impossible to discriminate whether cranial erosion is a result of the local destruction of CRDD or concomitant primary RDD of the bone involving the overlying skin without obtaining a sample from cranium.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our patient, 2 patients who presented with subcutaneous lesions on the scalp and underlying calvarial RDD have been reported recently 10 , 13 ; 1 of the patients also developed a lesion in the spine later. 13 Although it is unlikely the cutaneous lesion was derived from RDD of the bone in our patient, it is impossible to discriminate whether cranial erosion is a result of the local destruction of CRDD or concomitant primary RDD of the bone involving the overlying skin without obtaining a sample from cranium. Nevertheless, the patient will need to be followed up closely with imaging studies to monitor the development of additional bone lesions.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, Chen et al reported a 41-year-old man with a subcutaneous mass affecting the CNS. The patient was treated with surgical excision ( 4 ). However, the patient developed a lesion in his spine and agreed to undergo additional surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It mostly affects cervical lymph nodes, but approximately 40% of cases have extranodal lesions ( 1 ). Destombes first reported this disease in 1965 ( 2 ), then Juan Rosai and Ronald Dorfman described this disorder 4 years later ( 3 , 4 ). RDD is considered primary cutaneous RDD (CRDD) if it is localized to the skin or subcutaneous tissue, and there are no systemic symptoms (fever, night sweats, weight loss).…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 lists the imaging configurations and the main clinical distinctions of T1w, T2w, ceT1w, and FLAIR with information retrieved from [64][65][66][67]. • Lower signal for a higher water content [66], such as in edema, tumor, inflammation, infection, or chronic hemorrhage [66] • Higher signal for fat [66] • Higher signal for subacute hemorrhage [66] Uses long TR and TE [64] • Higher signal for a higher water content, such as in edema, tumor, infarction, inflammation, infection, or subdural collection [66] • Lower signal for fat [66] • Lower signal for fibrous tissue [66] 1w Uses the same TR and TE as T1w; employs contrast agents [64] • Higher signal for areas of breakdown in the bloodbrain barrier that indicate induced inflammation [65] IR Uses very long TR and TE; the inversion time nulls the signal from fluid [67] • Highest signal for abnormalities [65] • Highest signal for gray matter [67] • Lower signal for cerebrospinal fluid [67] * Pictures from [68]. TR, repetition time.…”
mentioning
confidence: 99%